Clinical utility of hematological parameters in aplastic anemia - Lizhong Zhang; Xiaonan Han; Qiujuan Zhu; Yu Qin; Yanan Jia (Scientific Reports)
Abstract Hematological parameters available on automated hematology analyzers have been shown to be useful indicators for hematological disorders. However, extensive studies especially in aplastic anemia for these indices are sparse. Our aim was to investigate the clinical utility of hematological parameters in aplastic anemia. The retrospective study included 146 patients with aplastic anemia and 150 normal controls matched in age and gender, where clinical characteristics and hematological parameters were classified and statistically analyzed. The study showed a statistical difference in the hematological parameters between aplastic anemia patients and controls. White blood cells, absolute neutrophil count, platelet, absolute reticulocyte count, mean reticulocyte volume, immature reticulocyte fraction, mean sphered cell volume, and light scattering reticulocyte count showed significant differences between non-severe aplastic anemia and severe aplastic anemia (p < 0.05). The analysis of the ROC curve showed that the hematological parameters were valuable for the differential diagnosis of severe aplastic anemia (areas under curve of white blood cell, absolute neutrophil count, platelet, absolute reticulocyte count, mean reticulocyte volume, immature reticulocyte fraction, mean sphered cell volume, light scatter reticulocytes were 0.620–0.859). Meanwhile, a combination of absolute neutrophil count, absolute reticulocyte count and mean sphered cell volume (AUC 0.893, 95% confidence interval 0.842–0.943, sensitivity 78.9%, specificity 85.7%) showed excellent precision for the differential diagnosis of severe aplastic anemia. Hematological parameters are readily available parameters that can be helpful to differentiate severe aplastic anemia from non-severe aplastic anemia. They may extend valuable prospects for clinical practice and research in aplastic anemia.